Unpredictable Regulatory Practices - World Bank (World Bank, Washington, DC, 2018)
The current regulatory environment in Bangladesh discourages the entry of innovative businesses.Entrepreneurs face a myriad of regulatory barriers including an absence of laws and regulations that clarify the rules of the game for new activities (regulatory gaps), and conflicting definitions and interpretations (regulatory ambiguity).Typically, rules and regulations are announced without prior notice, consultation or impact assessment. As a result, they do not benefit from the practical knowledge that businesses have. Even welldesigned rules and regulations cause problems if announced suddenly and with immediate effect.There are inconsistencies and gaps in rules and regulations.Government agencies often impose their own rules and procedures without considering possible conflicts with rules and procedures imposed by other government agencies.Businesses find it difficult to find information on existing rules and regulations.Regulatory officials use undue discretion in dealing with businesses.Many regulatory areas lack an effective grievance redressal system.Insecure property rights also dis-incentivize businesses from making investments.Regulatory unpredictability hampers business entry and day to day business operations; however, the degree depends on the size of the business.